The Importance of Information Culture in The Age of Globalization (Global Scientific Review, 2023)
The article talks about the fundamental changes in the social lifestyle as a result of the information and computer revolution, the objective basis and factors of the formation of information culture among young people in the era of globalization, as well as the means and methods